Improving The Efficiency Of Management Of Investment Potential In The Development Of Food Industry Enterprises (In The Case Of Kashkadarya Region) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In this article scientifically substantiated proposals have been developed to improve the efficiency of foreign investment by rationally attracting foreign investment in promising industries that determine the "points of growth" of the regions by using the method of hierarchical analysis.